Ecocracy dalam Pengembangan Destinasi Pariwisata - Erma Ariyani; Priskadini April Insani; Trysilvana Azwari (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2020)
In a democratic country, it certainly puts forward the principles of democracy. In this time, the tourism industry in Indonesia has great potential in the Indonesian economy. Along with its development, government policies in developing tourism destinations that have the potential to increase foreign exchange are expected to be sustainable development. Especially in terms of the environment where the concept of ecocracy itself is a form of recognition of nature. In this article use literature studies. The results obtained are addressing all government policies relating to the tourism sector without disrupting existing ecosystems. So that there needs to be steps that must be carried out by the government and there needs to be steps that must be taken for businesses in the tourism industry. Without harming people's rights around the tourism destination that will be developed.